Adolopment of adult diabetes mellitus management guidelines for a Pakistani context: Methodology and challenges - Martins, Russell Seth; Masood, Muhammad Qamar; Mahmud, Omar; Rizvi, Nashia Ali; Sheikh, Aisha; Islam, Najmul; Khowaja, Anum Naushad Ali; Ram, Nanik; Furqan, Saira; Mustafa, Mohsin Ali; Aamdani, Salima Saleem; Pervez, Alina; et al. (Frontiers in Endocrinology, 2023)
Abstract Introduction Pakistan has the highest national prevalence of type 2 diabetes mellitus (T2DM) in the world. Most high-quality T2DM clinical practice guidelines (CPGs) used internationally originate from high-income countries in the West. Local T2DM CPGs in Pakistan are not backed by transparent methodologies. We aimed to produce comprehensive, high-quality CPGs for the management of adult DM in Pakistan. Methods We employed the GRADE-ADOLOPMENT approach utilizing the T2DM CPG of the American Diabetes Association (ADA) Standards of Medical Care in Diabetes – 2021 as the source CPG. Recommendations from the source guideline were either adopted as is, excluded, or adapted according to our local context. Results The source document contained 243 recommendations, 220 of which were adopted without change, 5 with minor changes, and 17 of which were excluded in the newly created Pakistani guidelines. One recommendation was adapted: the recommended age to begin screening all individuals for T2DM/pre-diabetes was lowered from 45 to 30 years, due to the higher prevalence of T2DM in younger Pakistanis. Exclusion of recommendations were primarily due to differences in the healthcare systems of Pakistan and the US, or the unavailability of certain drugs in Pakistan. Conclusion Our newly developed guidelines recommend earlier screening for T2DM in Pakistan, due primarily to the higher prevalence of T2DM amongst younger individuals in Pakistan. Moreover, the systematic methodology used is a significant improvement on pre-existing T2DM CPGs in Pakistan. Once these evidence-based CGPs are officially published, their nationwide uptake should be top priority. Our findings also highlight the need for rigorous expanded research exploring the effectiveness of earlier screening for T2DM in Pakistan.